Conjugate Observation of Magnetospheric Chorus Propagating to the Ionosphere by Ducting. Issue 23 (28th November 2021) - Shen, Yangyang; Chen, Lunjin; Zhang, Xiao‐Jia; Artemyev, Anton; Angelopoulos, Vassilis; Cully, Christopher M.; James, H. Gordon; Yau, Andrew W.; Howarth, Andrew D.; Bortnik, Jacob; Wu, Jiashu; Tian, Sheng; et al.
Abstract: Whistler‐mode chorus waves are critical for driving resonant scattering and loss of radiation belt relativistic electrons into the atmosphere. The resonant energies of electrons scattered by chorus waves increase at increasingly higher magnetic latitudes. Propagation of chorus waves to middle and high latitudes is hampered by wave divergence and Landau damping but is promoted otherwise if ducted by density irregularities. Although ducting theories have been proposed since the 1960s, no conjugate observation of ducted chorus propagation from the equatorial magnetosphere to the ionosphere has been observed so far. Here we provide such an observation, for the first time, using conjugate spacecraft measurements. Ducted chorus waves maintain significant wave power upon reaching the ionosphere, which is confirmed by ray‐tracing simulations. Our results suggest that ducted chorus waves may be an important driver for relativistic electron precipitation. Plain Language Summary: We present magnetically conjugate observations of chorus waves propagating from the magnetosphere to the topside ionosphere and subsequently to the ground in ducted mode, that is, guided by density crests as light by optical fibers. In our case event, ducted chorus waves maintain significant wave power upon reaching the ionosphere, which is confirmed by ray‐tracing simulations. In addition, ducted chorus elements observed in the ionosphere bear similar timescales and repetition rates (<1 s) to previously reported microburst precipitation. Our observations imply that ducted chorus waves may be an important driver of relativistic electron precipitation from the Earth's radiation belt. Key Points: We report first conjugate observations of ducted chorus waves propagating from the equatorial magnetosphere to the ionosphere Ducted chorus waves maintain significant wave power upon reaching the ionosphere, which is confirmed by ray‐tracing simulations Ducted chorus elements bear similar duration and repetition rates to previously reported energetic microbursts